Rehabilitation Methods for Deformed Rigid Pavements Based on Research and Characterization - Cajamarca (LACCEI, 2024)
This research work was carried out with the purpose of characterizing the treatment methods for rigid pavements deterioration based on research already carried out for the city of Cajamarca, a non-experimental design was applied in which 19 investigations were compiled between scientific articles, theses and books, from which data such as the serviceability index structural number, cost per m², useful life, required thicknesses, dimensions of the structural parts of the road, evaluation and current state of the roads by PCI method, VIZIR were taken., among others. Two types of records were used as data collection instruments, in order to process the data and to carry out the statistical study, the Excel program was used. The results show that the characteristics found in the investigations such as the loss of serviceability, structural numbers, cost, useful life time, required thicknesses, are very important because when comparing them with each other and seeing the benefits and cons, the best method of maintenance can be defined. treatment that we can use for the rehabilitation of rigid pavements. Therefore, it is concluded that the best method of treatment of deteriorated rigid pavements is the overlay of reinforcements since it has the best characteristics that are the cost of rehabilitation per m² as it is economical, the useful life time that is added to the paving, the structural characteristics of the payment such as the resistance it acquires, the serviceability and the conformity of the user, and it is the most feasible to carry out in Cajamarca, all this